2018
DOI: 10.1002/mp.13061
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial assessment of aggressive prostate cancer by physio‐chemical photoacoustics: An ex vivo study with intact human prostates

Abstract: The proposed procedure has shown promises in the diagnosis of aggressive prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 37 publications
(92 reference statements)
1
45
0
Order By: Relevance
“…In the future, the proposed TUT could be integrated in conventional optical-microscopy techniques to allow multimodal microscopy that is capable of both ultrasound stimulation and sensing. Eventually, the TUT technology could be further scaled to develop miniaturized photoacoustic endomicroscopy and microendoscopy devices for space-constrained point-of-care clinical applications, e.g., prostate and pancreas needle biopsies [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…In the future, the proposed TUT could be integrated in conventional optical-microscopy techniques to allow multimodal microscopy that is capable of both ultrasound stimulation and sensing. Eventually, the TUT technology could be further scaled to develop miniaturized photoacoustic endomicroscopy and microendoscopy devices for space-constrained point-of-care clinical applications, e.g., prostate and pancreas needle biopsies [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) has also been used in the assessment of prostate cancer [1417]. However, patients with prostates that are suspected of being cancerous through MRI assessment still typically require a biopsy for confirmation of the prostate cancer [14, 15, 18]. Thus, there is a need to develop novel techniques for detecting prostate cancers through noninvasive means.…”
Section: Introductionmentioning
confidence: 99%
“…Angiogenesis and lipid accumulation have been shown to be increased in prostate cancer tumors [58,59]. In vivo [43] and ex vivo [34,35,41] imaging of human prostates have shown differences between malignant and benign prostate tissue using endogenous contrast. We have recently shown that successful prostate cancer biopsy targeting in ex vivo human prostates is possible using 1064 nm PAT and US imaging [34].…”
mentioning
confidence: 99%
“…While PAT has the potential to provide real-time biopsy targets, current PAT setups have not yet demonstrated the ability to image the full posterior-anterior depth as observed from the rectum with the US transducer [34,35,[41][42][43]. Two locations for the placement of the light delivery source for PAT have been investigated.…”
mentioning
confidence: 99%
See 1 more Smart Citation